DIGITAL MARKETING INNOVATION AS AN ACCELERATOR OF COMPETITIVE ADVANTAGE OF CULINARY MSMES: A LITERATURE STUDY IN THE FOOD & BEVERAGE SECTOR - Roza Thohiri; Mutiara Jihan Daulay; Meri Tarihoran; Lailan Hafizah Harahap; Natalia Kartika Simanjuntak; Shella Ardila; Hamidah; Wasti Maldini Sihombing (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of digital technology has transformed marketing strategies across various business sectors, including micro, small, and medium enterprises (MSMEs) in the culinary industry. This study aims to analyze the role of digital marketing innovation in enhancing the competitive advantage of MSMEs in the food and beverage sector. The research employs a systematic literature review approach by examining scientific articles published between 2018 and 2025 obtained from academic databases such as Google Scholar, Garuda, and Scopus. The findings indicate that digital marketing innovation contributes to improving brand visibility, strengthening customer engagement, expanding market reach, and enhancing customer experience. However, MSMEs still face several challenges, including limited digital literacy and insufficient marketing innovation capabilities. Therefore, the effectiveness of digital marketing implementation depends on the ability of business actors to strategically integrate digital technologies into their marketing activities.